2020
DOI: 10.1038/s41591-020-0751-5
|View full text |Cite
|
Sign up to set email alerts
|

Using human genetics to understand the disease impacts of testosterone in men and women

Abstract: Testosterone supplementation is commonly used for its effects on sexual function, bone health and body composition, yet its effects on disease outcomes are unknown. To better understand this, we identified genetic determinants of testosterone levels and related sex hormone traits in 425,097 UK Biobank study participants. Using 2,571 genome-wide significant associations, we demonstrate the genetic determinants of testosterone levels are substantially different between sexes, and that genetically higher testoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

56
561
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 475 publications
(664 citation statements)
references
References 52 publications
56
561
7
1
Order By: Relevance
“…Our observational and MR analyses provide strong evidence that men with higher circulating IGF-I have an elevated risk of prostate cancer; further, our observational analyses suggest a higher risk of prostate cancer mortality in these men, suggesting that IGF-I is associated with risk for more severe forms of prostate cancer and/or may increase the risk of prostate cancer progression. Higher serum free testosterone was associated with a higher risk of prostate cancer diagnosis, which is supported by a recent MR analysis 9 . We also found that men with higher SHBG had a lower risk.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Our observational and MR analyses provide strong evidence that men with higher circulating IGF-I have an elevated risk of prostate cancer; further, our observational analyses suggest a higher risk of prostate cancer mortality in these men, suggesting that IGF-I is associated with risk for more severe forms of prostate cancer and/or may increase the risk of prostate cancer progression. Higher serum free testosterone was associated with a higher risk of prostate cancer diagnosis, which is supported by a recent MR analysis 9 . We also found that men with higher SHBG had a lower risk.…”
Section: Discussionsupporting
confidence: 55%
“…Epidemiological studies have also reported an inverse association between prostate cancer risk and circulating SHBG 8 , although results from MR analyses are inconclusive 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Sex hormone supplementation has commonly effects on metabolic traits, sexual function and bone health [23]. Epidemiological study has indicated strong correlations between sex hormone supplements and health conditions [15].…”
Section: Discussionmentioning
confidence: 99%
“…The sex hormone associated SNPs was driven from a published GWAS [23]. Brie y, the study analyzed four sex hormone traits, including sex hormone-binding globulin (SHBG), testosterone, bioavailable testosterone and estradiol.…”
Section: Gwas Data Of Sex Hormone Related Traitsmentioning
confidence: 99%
“…Additionally, Belsky et al [22] observed that individuals at higher PRS were more likely to persist longer in smoking heavily and develop nicotine dependence more frequently. Recently, Katherine et al [23] conducted a two-stage GWAS in 425,097 United Kingdom (UK) Biobank study participants and identi ed 2,571 genetic variant-sex hormone associations. Using the PRS of sex hormone as instrumental variables, we can calculate the PRS of sex hormone and explore the correlations between PRS of sex hormone and mental traits.…”
Section: Introductionmentioning
confidence: 99%